Pemberdayaan Kelompok Wanita Tani melalui Program Pekarangan Pangan Lestari: Studi Kelompok Wanita Tani Kalolok Kelurahan Batupapan Kecamatan Makale Kabupaten Tana Toraja - Rante, Damaris; Rahman, Syamsul; Yunus, Awaluddin (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The Sustainable Food Yard Program (P2L) has great potential in improving food security and women's empowerment, but there are still gaps related to the effectiveness of the program in areas with certain geographical and social characteristics such as Kalolok Village, therefore this study is expected to provide theoretical contributions in the development of community-based empowerment models as well as practical contributions for village governments and stakeholders in designing sustainable empowerment strategies. This study uses the SWOT Analysis Method (Strengths, Weaknesses, Opportunities, Threats Analysis). SWOT is used to evaluate the strengths, weaknesses, opportunities and threats of the empowerment strategy applied to the Women Farmers Group (KWT) in the Context of the P2L Program in Batupapan Village. The results of the study using SWOT analysis The results of the IFAS analysis (2.67) and EFAS (2.57) indicate that the position of KWT Kalolok is in Quadrant I (Aggressive Strategy). This means that the group possesses significant internal strength and is supported by significant external opportunities. Therefore, development strategies need to focus on cultivation expansion, commodity diversification, technological innovation, marketing strengthening, and institutional development and internal capital. Therefore, developing cultivation innovations such as vertical farming/hydroponics is necessary to maximize limited land and providing intensive mentoring to assist in marketing produce through villages, village-owned enterprises (BUMDes), and local MSME networks.